Implementation of Computational Thinking and Ignatian Pedagogy in Geometry subject for Elementary School Pre-Service Teachers - Aprinastuti, Christiyanti (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to describe the implementation of Computational Thinking in the flipped classroom in the Geometry course based on Ignatian Pedagogy for prospective elementary school teachers at Sanata Dharma University. The research method used is descriptive. The research subjects were pre-service teacher Sanata Dharma University class 2017. The data collection techniques used were observation, interviews, and documentation. The data were analyzed by using qualitative analysis. This research concludes that the implementation by learning steps, namely (1) context, (2) experience, (3) action, (4) evaluation, (5) reflection. In this step, four aspects of Computational Thinking are developed, namely (1) decomposition, (2) pattern recognition, (3) abstraction, (4) algorithm. The results of the learning reflection show the response that students like the learning design.